Writing Difficulties in Dysgraphic Students: A Study Using Word Board Media - Dahlia, Eva; Amriyah , Chairul; Ningrum, Ayu Reza (Journal Corner of Education, Linguistics, and Literature, 2025)
This study investigates the writing difficulties experienced by students with dysgraphia and evaluates the effectiveness of Word Board media as an instructional intervention. The objective of this research is to identify specific patterns of writing challenges among students with dysgraphia and to assess the impact of a multisensory teaching tool in overcoming those challenges. The study involved 20 students from MI Al-Hidayah and MIS Nurul Asyrof, consisting of 10 students from grade 2 and 10 from grade 3. The participants were selected using purposive sampling based on signs of writing difficulties. A qualitative descriptive approach was employed, using classroom observation, interviews, and document analysis for data collection, while thematic analysis was used to interpret the findings. The results revealed consistent issues such as confusion between visually similar letters (e.g., "b" and "d"), substitution of letters with numbers (e.g., "s" as "5"), irregular spacing, inconsistent capitalization, and letter reversal. After a four-week intervention using Word Board media, students demonstrated improvements in letter differentiation, spacing, motor coordination, and writing confidence. These findings suggest that Word Board media is a practical, low-tech, and inclusive solution for supporting literacy development among students with learning difficulties. The study contributes to the fields of educational psychology and inclusive education by emphasizing the importance of multisensory teaching strategies in early literacy instruction.